2020
DOI: 10.1109/jsyst.2019.2900090
|View full text |Cite
|
Sign up to set email alerts
|

Secure Transmit Antenna Selection Protocol for MIMO NOMA Networks Over Nakagami-m Channels

Abstract: In this paper, we consider a multi-input multioutput (MIMO) non-orthogonal multiple access (NOMA) network consisting of one source and two legitimate users (LUs), so-called near and far users according to their distances to the source, and one passive eavesdropper, over Nakagami-m fading channels. Specifically, we investigate the cases where the signals of the far user might or might not be successfully decoded at the eavesdropper and the near user. Thus, we aim to design a transmit antenna selection (TAS) sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 32 publications
(85 reference statements)
0
23
0
2
Order By: Relevance
“…Due to Kong et al [40] confirmed that the factors include number of users, path-loss exponent, the number of antennae impacted on system performance. We therefore set the parameters for two users U 1 and U 2 and an eavesdropper E, path-loss exponent r = 4 [41]. We subjected the parameters to analysis and simulate as shown in Table 1.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to Kong et al [40] confirmed that the factors include number of users, path-loss exponent, the number of antennae impacted on system performance. We therefore set the parameters for two users U 1 and U 2 and an eavesdropper E, path-loss exponent r = 4 [41]. We subjected the parameters to analysis and simulate as shown in Table 1.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Some important and recent studies similar to this research are [36][37][38][39][40][41][42][43]. In the excellent work [36], the authors investigated SOP for the cooperative NOMA (C-NOMA) in CR networks and took into account the impact of distance of users from the BS on secrecy performance.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The outage probability (OP) performance of the joint AS algorithms proposed in Yu et al is studied for the cases of fixed power coefficients and optimized ones in Li et al and Yu et al, respectively. The secrecy OP performance of the NOMA networks has been investigated for different TAS schemes in previous works . The OP and ergodic sum‐rate performances have been analyzed in Aldababsa et al for the NOMA network with maximal ratio combining (MRC).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of works investigated some related issues such as performance of energy harvesting DF/AF relaying, cooperative, cognitive, and MIMO NOMA networks [12][13][14][15]. In addition, the work of [16] studied the secrecy performance of MIMO NOMA system over Nakagami-m channels with transmit antenna selection protocol. However, almost in these works the information sources are assumed that it can transmit RF energy and information by using TS or PS scheme.…”
Section: Introductionmentioning
confidence: 99%